การศึกษาสภาพวิสาหกิจชุมชนทางด้านการบริหารจัดการโลจิสติกส์ กรณีศึกษากลุ่มสตรีสหกรณ์บ้านคึมมะอุ-สวนหม่อน ต.หนองหว้า กิ่งอำเภอบัวลาย จังหวัดนครราชสีมา: A study of State of Community Enterprise for Logistic Management, Case Study : Ban Kuem Ma U-Suan Mon Women Co-operative, Nongwa Sub-district, Bualai District, Nakhon Ratchasima Chalerm Phra Kiat District, Nakhon Ratchasima - Lertyingyot, Siriporn (Asian Health, Science and Technology Reports, 2010)
The objectives of this research were first, to study general data study and opinion of logistic management of Ban Kuem Ma U-Suan Mon Women Co-operative Second, to study problem in aspect of logistic management of Ban Kuem Ma U-Suan Mon Women Co-operative by using Quantitative and Qualitative Research, were selected by means of purposive sampling. The two sample groups were 40 member and 7 committee of Ban Kuem Ma U-Suan Mon Women Co-operative. The results data were analysed by descriptive analysis using Mean and Percentage.The result that state of activities process of Ban Kuem Ma U-Suan Mon Women Co-operative same as logistic management 9 activities. There were 1) Inventory Management 2) Purchasing and Negotiation 3) Materials Management 4) Transport Management 5) Warehouse Management 6) Materials Handling 7) Customer Services 8) Packaging 9) Information Technology. There were a moderate level of the opinion of Ban Kuem Ma U-Suan Mon Women Co-operative, and it classified the opinion of member 3 levels. A high level was package aspect. 7 moderate levels were customer service, 7) Customer Services 5)Warehouse Management 2) Purchasing and Negotiation 3) Materials Management 4) Transport Management 6) Materials Handling 1) Inventory Management. A low most of problem were incomplete of information system. The result of committee interview found that the most of problem were incomplete of information Technology for interactive data, connection of data were not complete and many mistakes. No forecast and planning for purchasing or selling in advance, it couldn’t evaluate to material purchasing. Beside that Warehouse Management were not good enough for stocking and classification. This research can be used to apply logistic management suitable with each community enterprise to save cost and efficiency improvement and effective in operation. We can used data for the way of related people of logistic structure improvement with community enterprise and suitable with state of internal process. Basic factors sample and government policy were to competition increasing and development potentiality community enterprise.